Effect of slab gravity load on slab-column connection with different compressive strengths. (January 2022) - Choi, Seung-Ho; Heo, Inwook; Kim, Jae-Hyun; Jeong, Hoseong; Lee, Sang-Hoon; Kim, Kang Su
Abstract: Current design codes specify the effective compressive strength of a column-slab connection when columns and slabs have different concrete compressive strengths. However, this approach assumes that no gravity load is applied to the slab. The gravity loads acting on the slab weakens the confinement of the slab-column connection and reduces the effective compressive strength of the column. Therefore, the effective compressive strength of the column specified in the current design code can be considered unsafe when gravity loads act on the slab, similar to the case of an actual structure. In this paper, the existing studies on slab-column connection, in which the gravity loads act on the slab, were comprehensively reviewed, and an effective compressive strength of the column based on the strain in the top slab reinforcement was proposed. In addition, three slab-column connections were fabricated, where the gravity loads acting on the slab and constraint condition of the slab were set as test variables, and axial load tests were conducted. Highlights: This study proposed the effective compressive strengths of columns with slab loads. Axial load tests with slab loads were conducted. The proposed model provided good estimation of the effective column strength. This study proposed a simplified model, and its accuracy was verified.